(3OjhGf adjJI GdMcejs - (3TgGH GdOjf CHheMeO CMeO Hf eMeO Hf Ydj Hf adjJI GdMcej,J (B731 (3g` s
(3ChdgG (B:s
(3hdeG cGf GdbGVj GdCLd GdaGVd GdcGed GddHjH TgGH GdOjf aef SHb GdChGFd, hRQi deMGSf CdaGXg Ydi SMHGf hGFd, hPgHJ aj GdTYQ cd ePgH aCHOY aj fXeg hCYQH s
(3BNQgG (B:s
(3eHJhQ hBNQ GdehLhO efg(B: (3Ydjc UdGI QHc cd jhe hCda JMjI efj GdjcG s
(3GdeDda cGf cGJH GdEfTGA aj GdOhdI GdQShdjIs
(3GfXQ Qbe (B1160 (3COH GdLRA GdChd ef GdUaMI GdKGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B14s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B178 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs